1998
DOI: 10.1046/j.1365-2427.1998.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Scales and frequencies of disturbances: rock size, bed packing and variation among upland streams

Abstract: Summary 1. Disturbance is an important source of variability in species composition and diversity, but application of disturbance models is contingent upon a very good understanding of the spatial scales and frequencies of disturbance. Such information is particularly lacking from streams. In this study, we measured the disturbance levels of rocks (defined here as the proportion of the original sample disturbed after 6 months) of differing sizes and positions within the stream bed and looked at the variation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 21 publications
10
107
1
Order By: Relevance
“…The lack of difference (P > 0.05) in rock movement among rock size classes for all categories of movement was surprising. Other studies have shown differences in rock movement by size class in response to spates (Downes et al 1998), but we observed no significant difference in movement by rock size class even during spate weeks. Rock placement along the transect in each site in our study was determined randomly, but all rocks in the study were equally loose and unembedded as compared to naturally placed rocks, which may have been partially embedded.…”
Section: Substrate Movementcontrasting
confidence: 88%
See 4 more Smart Citations
“…The lack of difference (P > 0.05) in rock movement among rock size classes for all categories of movement was surprising. Other studies have shown differences in rock movement by size class in response to spates (Downes et al 1998), but we observed no significant difference in movement by rock size class even during spate weeks. Rock placement along the transect in each site in our study was determined randomly, but all rocks in the study were equally loose and unembedded as compared to naturally placed rocks, which may have been partially embedded.…”
Section: Substrate Movementcontrasting
confidence: 88%
“…The hydrologic forces within streams work primarily upon the substrate in a downstream direction and during spate conditions these forces are magnified by increased velocity and discharge. Spates are known to mobilize the streambed and move rocks of varying sizes downstream (Boulton et al 1992;Cobb et al 1992;Downes et al 1998;Death 2002;Death 2003;Gjerlov et al 2003). We also observed increased downstream movement of all rock sizes during spate flow conditions compared to baseflow conditions (Bossley 2016).…”
Section: Substrate Movementmentioning
confidence: 49%
See 3 more Smart Citations